Performance Overview of Licin Public Health Center in Tuberculosis Control Based on the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) - Fitria Nina Agustin; Diansanto Prayoga (Knowledge Dynamics, 2025)
Background: Tuberculosis (TB) remains a global health threat, with a death toll reaching 1.3 million. Indonesia has set a target to eliminate TB by 2030, with a treatment success rate of 90%. However, the achievement at Licin Public Health Center in Banyuwangi Regency in 2023 was only 76%, indicating the need for performance evaluation. This study aims to describe the performance of Licin Public Health Center in TB control based on the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). Methods: This study employed a descriptive quantitative approach with a cross-sectional design. The research sample consisted of 12 TB officers and 29 TB patients. Data were collected through questionnaires completed by the respondents and analyzed using the Baldrige Assessment. Results: The results showed that the performance of Licin Public Health Center was at the benchmark leader level with an excellent rating, achieving a score of 796.3 points out of a possible 1,000. The highest percentage score was found in the Workforce Focus category, while the lowest was in Strategic Planning, indicating strengths in human resource management and areas for improvement in long-term program planning. Conclusions: The performance of Licin Public Health Center in tuberculosis control ranks as superior among similar organizations, both at the regional and national levels. Nevertheless, improvements are still needed in areas such as organizational structure, strategy, patient satisfaction, and budget utilization to support the sustainable success of TB treatment.